Practical bone marrow cytology in the dog and cat - MYLONAKIS (Μ.Ε. ΜΥΛΩΝΑΚΗΣ) M. E.; HATZIS (Α. ΧΑΤΖΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2017)
In companion animal medicine, bone marrow (BM) aspiration cytology is a cost-effective diagnostic tool, which provides excellent morphological detail of cells and infectious agents. The major indications for BM aspiration include unexplained clinical manifestations (e.g., fever, body weight loss), persistent hematological or biochemical abnormalities (e.g., anemia, leukocytosis), diagnosis and/or staging of malignancies (e.g., lymphoma, mast-cell tumor), diagnosis of important infectious diseases such as leishmaniosis (Leishmania infantum) and canine monocytic ehrlichiosis (Ehrlichia canis) and evaluation of canine iron stores. Complications associated with BM aspiration are rare and the equipment and supplies required minimal, hence accounting for the popularity of this procedure in the clinical setting compared to BM core biopsy. This review focuses on the technical details pertaining to the collection of BM aspirate material, including the usual anatomic sites for sampling, the equipment required, the preparation of the animal, the aspiration technique and the BM material processing for good quality slide preparation. The description of the cellular population normally anticipated in the BM of the dog and cat and the systematic approach in evaluating and interpreting the BM cytological findings are also highlighted. In the last part of this review, the current classification guidelines for the canine and feline BM malignancies are briefly outlined.